PROBLEM-SOLVING METHODS INFLUENCING MATHEMATICS LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS IN PALANGKA RAYA - Muhran; Sion, Holten; Endang Mugi Rahayu, Sri; Rahan, Netto; Kuswari; Rahman Azahari, Abdul (Acta Scientiae et Intellectus, 2024)
The problem-solving method has advantages, especially it can make school education more relevant to life, the teaching and learning process through problem-solving can accustom students to face and solve problems skillfully. This method stimulates the development of students' thinking abilities creatively and thoroughly because in the learning process students do a lot of mental action by highlighting problems from various aspects to find solutions. The application of the problem-solving method makes students more skilled in solving problems related to math problems. Problem-solving methods will also help students understand because they relate to everyday life. Students can also practice their numeracy skills based on correct mathematical concepts when solving problems because students learn based on a systematic process. Also, students are facilitated to work together in groups and respect other people's opinions when solving problems, and foster motivation to learn. Problem-solving methods can have a significant effect on student mathematics learning outcomes.